Scenario Planning Model for Counterintelligence Strategy Against Foreign Intelligence Operations in Indonesia - Husein Sagaf (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
Foreign intelligence operations continue to occur within Indonesian territory despite existing regulatory frameworks governing state intelligence. This phenomenon reveals Indonesia's territorial vulnerabilities driven by the attraction of natural resources and weaknesses in counterintelligence governance following the 1998 Reformasi. This study aims to analyze Indonesia's vulnerabilities to foreign intelligence operations and formulate a scenario planning-based counterintelligence strategy model. The research employs qualitative methods through in-depth interviews with national intelligence stakeholders, Focus Group Discussions (FGD), and document analysis. Data were analyzed using the TAIDA framework (Tracking, Analyzing, Imaging, Deciding, Acting). Interviews were conducted with representatives from various intelligence and national security agencies while maintaining informant confidentiality in accordance with research ethics. Findings reveal that Indonesia's vulnerabilities stem from three main factors: the attraction of natural resources, legal gaps in prosecuting espionage/sabotage, and institutional fragmentation characterized by sectoral intelligence governance. The scenario planning model identifies four scenarios based on two critical driving forces: internal intelligence governance cohesion and external foreign intelligence operation intensity. Based on current conditions and intelligence practitioners' perspectives, Indonesia is positioned in Scenario 2 (weak internal cohesion, high external intensity), indicating foreign intelligence dominance. The most relevant current strategies are strengthening BIN's coordination role and implementing reverse operations. This study recommends strengthening the legal foundation through revising the State Intelligence Law or creating a comprehensive National Security Law to establish espionage/sabotage as criminal offenses with clear sanctions.